Children of the Great Depression - Freedman, Russell (Clarion Books, 2005)
Presents a collection of illustrated archival photographs describing children of the Great Depression, and draws upon memoirs, diaries, letters, and other first-hand accounts that look at the lives of young Americans during the 1930s.